College accounting : Single proprietorship for service and merchandising businesses, special journals, voucher system and payroll accounting - Harina, Ricardo M. (Mandaluyong City : National Book Store, 2003)
Each chapter begins with learning objectives. These objectives both preview and review the chapter content.
CHAPTER 1. Introduction to accounting -- 2. Analyzing and recording business transactions -- 3. Matching and adjusting process -- 4. Completing the accounting cycle for service business -- 5. Accounting for merchandising business -- 6. Cash and internal control -- 7. Using special journals in an accounting system -- 8. The voucher system and combination journal -- 9. Payroll Accounting.
Keywords: ACCOUNTING